INDUSTRI KREATIF KEBAHASAAN POTENSI MEDIA PEMASYARAKATAN DWIBAHASA - Dendy Sugono (SAWERIGADING, 2013)
In the early twentieth age, the growth and development of creative industry occur such as: film, video,photography, music, performance, architecture, handycraft, fiction and nonfiction books, publishing,advertisement, interactive game, and so on. The reserach of creative industry illustrates the bigpotential of creative industry which is based on language and supported by language. The potentialof creative industry could have effect through collaboration movement of language institution with thebusinessmen ofcreative industry in the motherland. The collaboration involvesfield worker, practitioner,andprofessionals (researcher, translater, dubber, designer, lexicographer, and training organizer), andlinguists, and lower and middle businessman. The handling of the growth and development of languagecreative industry is very strategic to socialize the use of both Indonesian and foreigner to promote theproduct of creative industry to the free market in Asean and Asia-Pasific area. Its success will drive theeconomy of the lower and middle society. AbstrakPada awal abad ke-21 ini telah terjadi pertumbuhan dan perkembangan di bidang industri kreatif:film, video, fotografi, musik, pertunjukan, arsitektur, kerajinan, karya fiksi dan nonfiksi, penerbitan/percetakan, periklanan, permainan interaktif, dan sebagainya. Penelitian tentang industri kreatif inimemperoleh gambaran betapa besar potensi industri kreatif berbasis bahasa dan industri kreatif berdayadukung bahasa. Potensi industri kreatif kebahasaan itu dapat diberdayakan melalui gerakan kolaborasilembaga pengelola kebahasaan dengan para pengusaha industri kreatif di tanah air. Kolaborasi itumelibatkan tenaga kerja lapangan, praktisi, kalangan profesional (peneliti, penerjemah, penyulih suara,perancang, pengolah kata, penyelenggara pelatihan), dan tenaga kebahasaan, serta pengusaha kecildan menengah. Penanganan pertumbuhan dan perkembangan industri kreatif kebahasaan itu sangatstrategis untuk masyarakatkan penggunaan dwibahasa Indonesia dan asing dalam pemasyarakatanproduk industri kreatif ke pasar bebas kawasan Asean ataupun Asia-Pasifik. Keberhasilan semua ituakan menggerakan ekonomi masyarakat kelas bawah dan kelas menengah.